Структурно-функциональная организация белков - Попов Евгений Митрофанович (Наука, 1992)
Экземпляры: КХ (20110504) / Инвентарный номер: 1009532 / Цена: 92.00 / Сис.шифр: 28.072 / Авт.знак: П 58 / ГРНТИ: 34 / ББК: 28.072.511.1